Unbored : the essential field guide to serious fun - Glenn, Joshua, 1967-; Larsen, Elizabeth Foy (New York : Bloomsbury USA, 2012)
"Unbored is the most original, entertaining, and instructive all-in-one book for kids ever published -jam-packed with information, ideas, and activities for children and their parents to share together. Vibrantly designed and illustrated, it's crammed with activities that are not only fun and doable, but get kids engaged in the wider world--and provides information to expand their worldviews, too, inspiring them to learn more. Right at the age where kids start to disappear into various screens, Unbored encourages them to use those tech skills in creative ways. Activities parents will remember from their childhoods are presented alongside bold new possibilities: science experiments, crafts and upcycling, board game hacking, code-cracking, geocaching, skateboard repair, yarn bombing, stop-action movie-making - plus tons of trivia, best-of lists, and forward-thinking ideas made accessible to kids. Unbored expertly walks the line between cool and constructive: parents will appreciate its wisdom and humor, its lessons in civic-mindedness and self-esteem, as well as its anti-perfectionist spirit. Kids will just think it's awesome"--
Shares ideas and activities to engage readers in the wider world, with information to expand their worldviews and encourage them to use their skills in creative ways, including science experiments, crafts and upcycling, and geocaching.
Keywords: Recreation -- Juvenile literature; Amusements -- Juvenile literature; Handicraft -- Juvenile literature; Games -- Juvenile literature; Recreation; Amusements; Handicraft; Games; CRAFTS & HOBBIES / General; GAMES / General; SPORTS & RECREATION / General; FAMILY & RELATIONSHIPS / Activities; REFERENCE / Handbooks & Manuals; FAMILY & RELATIONSHIPS / Parenting / Child Rearing; JUVENILE NONFICTION / Curiosities & Wonders; JUVENILE NONFICTION / Activity Books; Recreation; Amusements; Handicraft; Games